To shred roughly or to grind? On the methods of sample preparation of the keratinous material for stable hydrogen isotope analysis - Maria A. Belova (Cherepovets State University, 2020)
Hydrogen stable isotope measurement in keratin samples (hair, feathers, etc.) is one of the very popular, but rather complex tasks of isotope ratio mass spectrometry. The complexity of such analyzes is associated with the rapid contamination of samples with hydrogen from atmospheric moisture. The effects of various methods of sample preparation on the measured values of δ2H is still an emerging issue in this field of study. The method of hair shredding practically does not affect the dynamics of the atmospheric moisture sorption by the samples. However, despite the same amount and isotopic composition of sorbed water, the measured δ2H values for roughly shredded and grinded hair can vary significantly and unpredictably. Equilibration the hair water content with the atmospheric moisture, even for a long time, does not completely erase the “isotope history” of the sample, which requires a review of standard sample preparation procedures.